The Role of Masturah Da'wah in Forming a Sakinah Family in The Jamaat Tablighi of Manado City - Bilalu, Naskur; Purwadi, Wira; Subeitan, Syahrul Mubarak (al-'adalah, 2022)
This paper discusses the formation of the sakinah family through the role of da'wah Masturah, a Jamaat Tablighi's program, namely da'wah efforts among women. Because the task of reviving religion lies not only on men but also on women, a sakinah family will be formed when every family member is obedient to Allah SWT. This study aims to determine the role of da'wah Masturah in forming a sakinah family in Jama'ah Tablighin Singkil District, Manado City. This research is field research with a qualitative nature whose data is collected through observation, interviews, and documentation related to the focus of research on the Jama'ah Tablighin Singkil District, Manado City. The results of this study show that da'wah Masturah is very influential in forming a sakinah family in Jama'ah Tabligh in Singkil District, Manado City. There are 3 (three) indicators that da'wah Masturah plays an important role in forming a sakinah family: First, every family member is obedient in carrying out religious orders; Second, husband and wife understand their rights and obligations; and; Third, children are expected to be a pious and/or pious generation